Effects of copper prices volatility on Peruvian economics: empirical evidence from TVP-VAR-SV models - Muñoz Aguilar, Jose Carlos (2024)
Considering the strong performance of copper prices in the past few years and the dependence on this mineral for Peru, this research was developed. with the objective to analyze the effects of copper prices volatility on these main macroeconomic variables. For this are proposed a TVP-VAR-SV model. The results indicate that a 1% rise in copper prices leads to a corresponding increase of 0.03% in GDP growth, an increases of 3.77% in exports and a decrease of 1.22% in exchange rate, on average, within the first quarter following the price change. However, it can be seen how the effects are amplified in periods of high volatility in the price of copper. In 2009Q4, these effects are amplified, where the GDP increases by 0.69%, exports increase by 5.86% and the exchange rate decreases up to 1.69%.